Asset Market and Balance of Payments Characteristics : An Eclectic Exchange Rate Model for the Dollar, Mark, and Yen - MacDonald, Ronald (IMF Working Papers; Working Paper ;, 1995)
In this paper we use an exchange rate model that combines asset market characteristics with balance of payments interactions to examine the nominal effective exchange rates of the German mark, Japanese yen, and U.S. dollar for the recent experience with floating exchange rates. Our approach may be interpreted as one which attempts to flesh out the missing links that arise in conditioning an exchange rate solely on relative prices, as occurs in a standard PPP analysis. In contrast to much other empirical exchange rate modeling, our approach explicitly involves the use of a current account sustainability term. Amongst the findings reported in this paper are: significant, and sensible, long-run relationships for all of the currencies studied; appealing short-run dynamics for two of the currencies; and a finding that the Japanese effective exchange rate closely tracks the long-run exchange rate defined in this paper.